Systemic and ophthalmological findings in Cornelia de Lange syndrome - Mrugacz, Małgorzata; Sielicka, Danuta (Klinika Oczna / Acta Ophthalmologica Polonica, 2012)
Cornelia de Lange Syndrome (CdLS, de Lange syndrome, Brachmann-de Lange syndrome), is a relatively rare genetic disorder, characterized by set of clinical abnormalities concerning different organs and systems. Phenotypic diagnosis is based on a specific dysmorphic features seen after the birth. We described a genetic basis, hereditary patterns, characteristic dysmorphic features and the most common clinical findings of patients Cornelia de Lange Syndrome concerning eye and vision, hearing, cardiovascular, respiratory, gastrointestinal, genitourinary, skeletal and psychomotor development.